Novel β-lactam antibiotics versus other antibiotics for treatment of complicated urinary tract infections: a systematic review and meta-analysis - Quan, Xiang hua; Wang, Xin yi; Han, Chun hua; Xing, Xiao min; Zhang, Bin; Cang, Huai qin (Frontiers in Pharmacology, 2024)
Objective: We conducted a systematic review with meta-analysis to explore the efficacy and safety of novel β-lactam antibiotics versus other antibiotics against cUTIs. Methods: PubMed, Embase, and the Cochrane Central Register of Controlled Trials were searched systematically from inception through March 15, 2024 for clinical trials comparing novel β-lactam antibiotics with other antibiotics for treatment of cUTIs. Random-effects models were used to evaluate the impact of treatment on the risk ratio (RR) of clinical response , microbiologic response, adverse effects (AEs), serious adverse effects (SAEs). The quality of evidence was evaluated with the Cochrane Risk of Bias assessment tool. The review was registered in INPLASY (INPLASY202440054). Results: Ten randomized controlled trials involving 5925 patients met our inclusion criteria. Our meta-analysis revealed that there was no significant difference in overall clinical response (RR = 1.02), AEs (RR = 1.07), SAEs (RR = 1.20)between novel β-lactam antibiotics groups and other antibiotics groups. However, a significant difference was found in a subgroup of clinical cure rates at the end of treatment between novel β-lactam antibiotics groups and carbapenems groups, with low heterogeneity (RR = 1.02). A significant difference was observed in microbiologic response (RR = 1.11). Subgroup analysis revealed a significant difference in microbiologic response between novel BBL/BLS groups and carbapenems groups (RR = 1.13, I2 = 21%, P = 0.005). Differences was observed between novel BBL/BLS groups and piperacillin/tazobactam sodium groups (RR = 1.21, I2 = 70%, P = 0.02). Similar results were obtained from subgroup analysis of the difference in microbiologic response between novel β-lactam antibiotics groups and ertapenem groups (RR = 0.92, I2 = 0, P = 0.01). Conclusion: Novel β-lactam antibiotics had similar overall clinical cure, AEs, SAE, to other antibiotics in the treatment of cUTIs. However, novel β-lactam antibiotics demonstrated superior clinical cure rates compared to carbapenems in a subgroup analysis, and exhibited better microbiologic response than other antibiotics.